Assessment of acute kidney injury in dogs suffering from babesiosis and leptospirosis - Asma Idrees; P.M. Deepa; K. Vinodkumar; R. L. Rathish; M. Pradeep (Journal of Veterinary and Animal Sciences, 2023)
Acute kidney injury (AKI) is a serious complication of infectious diseases like babesiosis and leptospirosis in dogs. Both the diseases show similar clinical manifestations, due to which timely differential diagnosis often gets delayed. The present study focused on diagnosis of major infectious agents causing AKI and its grading in dogs. Peripheral blood smear examination and PCR were used for the diagnosis of babesiosis. Leptospirosis was screened using PCR and MAT and was later confirmed by MAT on paired sera sample. Diagnosis of AKI was made based on the increase in serum creatinine levels ≥0.3 mg/dL within 48 h of presentation. Staging of animals was carried out as per International Renal Interest Society (IRIS) guidelines. All the dogs with confirmed leptospirosis and 15 per cent of dogs with babesiosis were diagnosed with AKI. The timely diagnosis of AKI in dogs during their initial stages helps to regain normal renal function within short-term treatment itself.